Pembatasan Import Sampah Sebagai Komitmen Indonesia Dalam Upaya Penanganan Perubahan Iklim Global - Sulistio, Prabowo; Syahruddin, Sri Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2024)
Indonesia is the second largest producer and contributor of waste in the world, both organic waste and plastic waste. Plastic waste has always been a major problem in environmental pollution, both land and sea pollution. Based on UN Comtrade data, in 2022 Indonesia has imported plastic waste as much as 30.4 million US Dollars with a volume of 53.76 million kilograms with the countries that export the most plastic waste to Indonesia are the Netherlands, Germany and Slovenia. In addition to the problem of unpreparedness in domestic waste processing, Indonesia also faces the problem of the large inflow of illegal waste which of course further burdens the burden of domestic waste processing. Waste, which is a source of pollution, is also one of several sources of greenhouse gases in the increasingly worrying problem of climate change, which then encourages research to find the right solution and handling strategy. The author in this paper uses descriptive qualitative methods. The strong commitment of the government in enforcing regulations and all stakeholders in waste management is the key to long-term environmental improvement.